Profile of Clinical and Radiological Factors of Intracerebral Hemorrhage Stroke Patients in Dr. Soetomo Hospital - Farizal Rizky Muharram; Asra Al Fauzi; Paulus Rahardjo; Pudji Lestari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: ICH (intracerebral hemorrhage) is a medical emergency with high mortality and morbidity that occurs in 15-20% of stroke cases. However, in the Multicenter Surgical Trial in Lobar ICH (STICH) study no benefit was found from the initial operative handler in Lobar ICH patients. Many clinical and radiological factors that affect outcomes of patients.Methods: The design of this study was a cross-sectional study. Clinical and radiological factors were analyzed by chi-square test and Kruskal-Wallis test. Then significant results were sought Relative RiskResults: This research was conducted from January 2017 to September 2018 starting from sampling to processing data. Sampling was carried out at the medical record center of Dr. Hospital. Soetomo Surabaya. Data collection is done by using secondary data in the form of patient medical records. All of the collected intracerebral hemorrhage patients were 302 and the total patients who met the inclusion and exclusion criteria were included in the study as the study subjects. Patients who met the criteria obtained 247 research subjects.Conclusion: There are several factors that influence the outcome of ICH stroke patients. Radiological factors and clinical factors both have an impact on outcomes. Further research is needed to find out which factors can be a diagnosis for choosing treatments that provide better outcomes. Statistically more than 1 variable is needed to determine an action that results in a more significant outcome of living patients. This shows that the choice of treatment for patients with different characteristics requires different treatments. Further analysis is needed to look for indications of the use of Operative or Conservative actions16.